Metode Pengukuran Volume Perdarahan Pemeriksaan MSCT Kepala pada Kasus Intraserebral Hemmorhage - Siti Masrochah; Rinda Yuliana Lestar; Luthfi Rusyadi (Poltekkes Kemenkes Semarang, 2021)
Background: Intracerebral hemorrhage is bleeding in the brain parenchyma. An accurate measurement of bleeding volume to determine the appropriate medical action. This study to determine the method of measuring the volume of intracerebral hemorrhage in MSCT examination of the head and determine the advantages and disadvantages between the manual method (Broderick, ABC's, Ellipsoid) and the software method (automatic volume, otsu).Methods: This type of descriptive qualitative research with the Literature Review. Data obtained by identifying problems then searching for keywords, looking for several journals sourced from databases such as Google Scholar, Science Direct, Springer. Data analysis by studying theoretically the method of measuring the volume of bleeding methods manually (Broderick, ABC’s, ellipsoid) and using software methods (automatic volume, otsu).Results: The results of measuring the volume of bleeding in the same patient with the manual method (Broderick) produce more bleeding volume (overestimate) that is 8750 mm3 from the 7960 mm3 automatic volume method. The manual method (Broderick, ABC’s, Ellipsoid) uses the ABC / 2 formula and uses 5 mm slice thickness, the automatic volume software method uses 1 mm slice thickness segmentation and technique, while the otsu software method uses 2.5 mm segmentation and slice thickness techniques.Conclusion: The advantages of the manual method (Broderick, ABC’s, ellipsoid) take approximately 1 minute to determine the estimated outcome of the bleeding volume, the weakness is higher in irregular bleeding. The advantages of the software method (automatic volume, otsu) in the use of precise segmentation techniques for accurate volume results, weaknesses are too long in determining the estimated bleeding volume results.